2011
DOI: 10.1093/jxb/err355
|View full text |Cite
|
Sign up to set email alerts
|

A male sterility-associated cytotoxic protein ORF288 in Brassica juncea causes aborted pollen development

Abstract: Cytoplasmic male sterility (CMS) is a widespread phenomenon in higher plants, and several studies have established that this maternally inherited defect is often associated with a mitochondrial mutant. Approximately 10 chimeric genes have been identified as being associated with corresponding CMS systems in the family Brassicaceae, but there is little direct evidence that these genes cause male sterility. In this study, a novel chimeric gene (named orf288) was found to be located downstream of the atp6 gene an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 49 publications
4
56
0
1
Order By: Relevance
“…Novel and chimeric mitochondrial sequences are a frequent result of this recombination (Wise et al, 1987;Kennell and Pring, 1989;Wen and Chase, 1999;Gallagher et al, 2002;Okazaki et al, 2013;Yamagishi and Bhat, 2014;Tang et al, 2017), in which recombination sometimes leads to the creation of transcripts that interfere with normal male gametophyte development (Kitazaki and Kubo, 2010) via the generation of toxic and/or disruptive transmembrane proteins (Korth et al, 1991;Kim et al, 2007;Wan et al, 2007;Zhang et al, 2007;Yang et al, 2009;Gulyas et al, 2010;Jing et al, 2012;Flores-Renteria et al, 2013;Ji et al, 2013;Luo et al, 2013;Okazaki et al, 2013;Park et al, 2013;Hu et al, 2014). Surprisingly, such genes are not only abundant in many fertile plants, such as Arabidopsis thaliana Unseld et al, 1997), Beta vulgaris (Kubo et al, 2000), Oryza sativa (Notsu et al, 2002), Brassica napus (Handa, 2003), Zea mays (Clifton et al, 2004), Triticum aestivum (Ogihara et al, 2005), and Nicotiana tabacum (Sugiyama et al, 2005), but are also constitutively expressed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Novel and chimeric mitochondrial sequences are a frequent result of this recombination (Wise et al, 1987;Kennell and Pring, 1989;Wen and Chase, 1999;Gallagher et al, 2002;Okazaki et al, 2013;Yamagishi and Bhat, 2014;Tang et al, 2017), in which recombination sometimes leads to the creation of transcripts that interfere with normal male gametophyte development (Kitazaki and Kubo, 2010) via the generation of toxic and/or disruptive transmembrane proteins (Korth et al, 1991;Kim et al, 2007;Wan et al, 2007;Zhang et al, 2007;Yang et al, 2009;Gulyas et al, 2010;Jing et al, 2012;Flores-Renteria et al, 2013;Ji et al, 2013;Luo et al, 2013;Okazaki et al, 2013;Park et al, 2013;Hu et al, 2014). Surprisingly, such genes are not only abundant in many fertile plants, such as Arabidopsis thaliana Unseld et al, 1997), Beta vulgaris (Kubo et al, 2000), Oryza sativa (Notsu et al, 2002), Brassica napus (Handa, 2003), Zea mays (Clifton et al, 2004), Triticum aestivum (Ogihara et al, 2005), and Nicotiana tabacum (Sugiyama et al, 2005), but are also constitutively expressed.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, such genes are not only abundant in many fertile plants, such as Arabidopsis thaliana Unseld et al, 1997), Beta vulgaris (Kubo et al, 2000), Oryza sativa (Notsu et al, 2002), Brassica napus (Handa, 2003), Zea mays (Clifton et al, 2004), Triticum aestivum (Ogihara et al, 2005), and Nicotiana tabacum (Sugiyama et al, 2005), but are also constitutively expressed. Research into this phenomenon has revealed much about the distribution and occurrence of CMS, the tissue-specificity of the phenotype (male gametophytic tissues only) (Jing et al, 2012;Hu et al, 2014), the modes of action behind CMS, and the cytonuclear cooperation that suppresses the phenotype (Carlsson et al, 2008). As more genomes (both nuclear and mitochondrial) and other "-omic" data become available (Du et al, 2016;Jacoby et al, 2016;Wang et al, 2016), the potential for increasing our understanding and manipulating this vitally important phenomenon will be enhanced.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, genes associated with CMS genes are located in the periphery of certain known mitochondrial genes and are cotranscribed with them [26]. T-urf13 ( orf115 ) was the first identified aberrant gene in the Texas (T)-cytoplasm of maize, which encodes a 13 kDa membrane-spanning polypeptide that depolarizes the mitochondria and leads to cell death [27-29].…”
Section: Introductionmentioning
confidence: 99%